2020
DOI: 10.1111/ajco.13409
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for prostate cancer: Effect of gold fiducial markers on diffusion‐weighted magnetic resonance imaging

Abstract: Purpose There has been an increase in the use of gold fiducial markers to ensure precise radiotherapy delivery in prostate cancer patients. However, metal artifacts may affect the quality of subsequent imaging used to assess disease status following treatment. In this study, we evaluated the effect of gold fiducial markers on magnetic resonance imaging (MRI), particularly on diffusion‐weighted imaging (DWI). Material and methods Among 57 patients with prostate cancer, 21 patients in whom two gold markers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A comparative study of the effects of gold composition on the artifacts caused by fiducial markers in CT and MRI images was reported by Tanaka et al 10,11 . Artifact generation in CT was slightly higher for the Gold Anchor than the VisiCoil, and visualization in MRI was slightly better for the Gold Anchor than the VisiCoil 12 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A comparative study of the effects of gold composition on the artifacts caused by fiducial markers in CT and MRI images was reported by Tanaka et al 10,11 . Artifact generation in CT was slightly higher for the Gold Anchor than the VisiCoil, and visualization in MRI was slightly better for the Gold Anchor than the VisiCoil 12 .…”
Section: Discussionmentioning
confidence: 92%
“…A comparative study of the effects of gold composition on the artifacts caused by fiducial markers in CT and MRI images was reported by Tanaka et al 10,11 Artifact generation in CT was slightly higher for the Gold Anchor than the Visi-Coil, and visualization in MRI was slightly better for the Gold Anchor than the VisiCoil. 12 In addition, Tanaka et al analyzed the effects on MRI images after inserting these two different gold markers individually into the prostate and revealed that diffusion-weighted imaging (DWI) in multiparametric MRI demonstrated negligible effects on DWI quality; therefore, they concluded that gold markers do not affect MRI quality, particularly DWI, and can be used during follow-up in prostate cancer patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This observation may be attributed to several factors, including incomplete neovascular endothelium within PCa tissues, increased blood supply, and enhanced water molecule diffusion, all of which collectively contribute to the lower ADC values in the peripheral zone [21][22][23]. Furthermore, when compared to patients with BPH, PCa patients also demonstrated lower ADC values in the peripheral prostate region, and this can be linked to PCa lesions characterized by low DWI signal and T2 shortening, as well as the presence of both T2 shortening and diffusion enhancement, both of which result in a decrease in DWI signal [24,25].…”
Section: Discussionmentioning
confidence: 99%